If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -6)(3x + -6) = 0 Reorder the terms: (-6 + 3x)(3x + -6) = 0 Reorder the terms: (-6 + 3x)(-6 + 3x) = 0 Multiply (-6 + 3x) * (-6 + 3x) (-6(-6 + 3x) + 3x * (-6 + 3x)) = 0 ((-6 * -6 + 3x * -6) + 3x * (-6 + 3x)) = 0 ((36 + -18x) + 3x * (-6 + 3x)) = 0 (36 + -18x + (-6 * 3x + 3x * 3x)) = 0 (36 + -18x + (-18x + 9x2)) = 0 Combine like terms: -18x + -18x = -36x (36 + -36x + 9x2) = 0 Solving 36 + -36x + 9x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '9'. 9(4 + -4x + x2) = 0 Factor a trinomial. 9((2 + -1x)(2 + -1x)) = 0 Ignore the factor 9.Subproblem 1
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {2, 2}
| 27-9x=4x+8 | | 4(x+9)+5x= | | 2x-5=?(x+4) | | (-15)+(-7)= | | 21x^4=2+x^2 | | 2-8x/1 | | 4(x+5)=3(x-6)+x | | -2(7-y)+4=44 | | 5/16*40n | | 6b^2-40=-8b+2b^2 | | .2-y=-.05x | | (x+9)(x-5)/(5x+4) | | -17+x/8=15 | | -2.6d-3.4d= | | 3(4x-6)=3(4x-3) | | 5/4=-5/3+s | | 23/4x=67/8 | | -4(5t-3)+8t=7t-2 | | (4x-6)=3(4x-3) | | x+6/5+x+3/x=3 | | 7y+5=-6y-21 | | 2z+2=2-2z | | 6x+20=4x-36 | | 4r+7=-43 | | n^2+n=2n | | 7h-10=-4 | | -1-7x-6(-7-x)=36 | | (2a+4b)(3a-b)=0 | | 7h-10=4 | | (7a-7)(6a-4)= | | (7a-7)(6a-4)= | | 4p+7p^2= |